y=x^3e^(tg3x)
y=ln(x^4-sin^3x)
Правило нахождения производной произведения:
(u*v)`=u`*v+u*v`
y`=(x^3*e^(tg3x))`=(x^3)`*e^(tg3x)+x^3*e^(tg3x)=
правило нахождения производной сложной функции
(e^(u))` = e^(u) * u`
=3x^2*e^(tg3x)+x^3*e^( tg3x)* [b](tg3x)`[/b]=
=3x^2*e^(tg3x)+x^3*e^( tg3x)* [b](1/cos^23x)*(3x)`[/b]=
=3x^2*e^(tg3x)+(3*x^3*e^( tg3x)* )/(cos^23x)
б)
Правило нахождения производной сложной функции
(lnu)`=u`/u
(ln( x^4-sin^3x))`=(x^4-sin^3x)`/(x^4-sin^3x)=
=(4x^3-3sin^2x*cosx)/(x^4-sin^3x)